Self-assembly of cuprous iodide cluster-based calix[4]resorcinarenes and photocatalytic properties. Issue 40 (29th September 2021) - Hu, Chu-Xing; Xuan, Ya-Hui; Jiang, Zi-Hao; Lu, Tao; Yang, Jie; Yuan, Hui; Tian, You-Ping; Sun, Zheng-Guang; Jiang, Xuan-Feng
Abstract : Cluster-based complexes 1 and 2 with [Cu6 I5 ] and [Cu8 I8 ] polynuclear motifs were constructed via a conformation-adaptive self-assembly strategy, respectively. Two Cu(i ) complexes exhibited photocatalytic activity to the CuAAC reaction in water solution. Abstract : The controlled self-assembly of cuprous iodide cluster-based supramolecular architectures with a tunable structure is still a big challenge to date. We adopt a conformation-adaptive self-assembly strategy to precisely construct two [Cu m I n ] calix[4]resorcinarenes including one-dimensional MOF 1 ({[Cu6 I5 ]2 [CuI2 ]3 (L 1 )3 } n ) with [Cu6 I5 ] tricubane cluster nodes and [Cu8 I8 ] type supramolecular cluster 2 ([(Cu8 I8 )L 2 2 ]) from ditopic cavitands L 1 –L 2 . Furthermore, such emissive complexes exhibited high photocatalytic activity to the azide–alkyne cycloaddition reaction (CuAAC) in water.